Kozmopolitizem kot identiteta Aleša Debeljaka - Jacek Kozak, Krištof (Slavia Centralis, 2020)
COSMOPOLITANISM AS ALEŠ DEBELJAK’S IDENTITYThe concepts of local and global today at present mean very much, yet, because of this, also very little. This question becomes particularly obvious in relation to culture, which cannot be kept within any borders whatsoever. Based on the literary and essayistic work of Aleš Debeljak – especially on the poet’s concept of cosmopolitism – the article tries to form a different approach to this question. A child of ex-Yugoslavia, Debeljak understood identity as the rippling of concentric circles from Slovenia through Yugoslavia to America. The article discusses thejuxtaposition of the concept of identity with the position of the local, global and positions in-between.
Keywords: Aleš Debeljak; cosmopolitanism; identity; global; local